Il diritto come civilizzazione della forza. Considerazioni su Freud e Kelsen. - Ciaramelli, Fabio (Teoria e Critica della Regolazione Sociale / Theory and Criticism of Social Regulation, 2024)
In this paper, I would like to present a possible way of understanding law and its function in terms of “Kulturarbeit (work of civilisation)” or, in other language, “social technique”, according to which, within the process of civilisation, the specificity of law is characterised by the task of civilising force, limiting the excesses of power, regulating and governing its violence and thus removing human events from the inexorability of the fait accompli, which then inevitably underlies the so-called “law of the strongest”. The result is an explication of the historically and socially instituted character of law, and consequently the need to evaluate and justify its legality.